2013
DOI: 10.1364/ome.3.001687
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Au-assisted planar GaAs nanowire growth by p-type dopant impurities

Abstract: III-V compound semiconductor nanowires (NWs), with their direct bandgaps and high mobilities, have been shown to be promising materials for many applications including solar cells, light emitting diodes, transistors, and lasers. Self-aligned, twin-plane-defect free, planar GaAs NWs can be grown by metalorganic chemical vapor deposition (MOCVD) through the Au-assisted vapor-liquid-solid mechanism. In this report, <110> planar GaAs NW growth on GaAs (100) substrates is perturbed by introducing common p-type dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
(43 reference statements)
3
21
0
1
Order By: Relevance
“…For the VLS-grown NW, the electrical resistance decreases from approximately 150 to 100 kΩ toward the NW's tip. Previous studies on p-type doping of VLS-grown NWs reported an accumulation of Zn impurities in the Au seed [10,15]. This indicates that even though the DEZn constantly flows in the reactor during the growth, the Zn doping impurities increasingly incorporate into the NWs through the Au seed.…”
Section: Shown Inmentioning
confidence: 90%
See 1 more Smart Citation
“…For the VLS-grown NW, the electrical resistance decreases from approximately 150 to 100 kΩ toward the NW's tip. Previous studies on p-type doping of VLS-grown NWs reported an accumulation of Zn impurities in the Au seed [10,15]. This indicates that even though the DEZn constantly flows in the reactor during the growth, the Zn doping impurities increasingly incorporate into the NWs through the Au seed.…”
Section: Shown Inmentioning
confidence: 90%
“…The incorporation of p-type dopants into VLS-grown III-V NWs, however, can lead to strong kinking or perturbation in the NW [10,15]. Furthermore, the VLS-grown InAs NWs are expected to have a large variation in the doping concentration along the NW length for two main reasons: (1) different incorporation rates of the dopant through the metal seed and the NW side facets [11] and (2) delayed incorporation of the p-type dopants from the metal seed during the growth process [15]. We have recently demonstrated the self-assembled growth of III-V NWs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although for Ge and many other VLS nanowires, it appears that most dopants reside in the thin epitaxial layers that form on the nanowire sidewalls due to the VPE growth [137,153], it has been confirmed that Zn incorporates primarily through the VLS growth in vertical [139] and planar [157] GaAs VLS nanowires. Although for Ge and many other VLS nanowires, it appears that most dopants reside in the thin epitaxial layers that form on the nanowire sidewalls due to the VPE growth [137,153], it has been confirmed that Zn incorporates primarily through the VLS growth in vertical [139] and planar [157] GaAs VLS nanowires.…”
Section: Doping Of Iii-v Nanowiresmentioning
confidence: 99%
“…The formation of twinning superlattices (TSLs) induced by p-type dopants has been reported in vertical nanowires [102,103,158,159], as well as in planar GaAs nanowires, which are otherwise free of twin-plane defects [157]. The formation of twinning superlattices (TSLs) induced by p-type dopants has been reported in vertical nanowires [102,103,158,159], as well as in planar GaAs nanowires, which are otherwise free of twin-plane defects [157].…”
Section: Doping Of Iii-v Nanowiresmentioning
confidence: 99%
“…Nanostructures possessing non-monotonous morphological variations along the growth direction are offering new avenues for device engineering, with periodic dimensional changes 13,16,20 of particular interest due to novel quantum confinement effects. [21][22][23][24] Moreover, the formation of preferentially orientated structures 25 are developed in parallel with advancing technological aims to employ bottom-up fabrication techniques.…”
mentioning
confidence: 99%